Kajian Ergonomi Untuk Perancangan Alat Bantu Angkat Brush Seal Welding Fixture Dengan Pendekatan Quality Function Deployment (Studi Kasus Pada PT Fluid Sciences Batam) - Heru Kusbiantoro; Sri Zetli (LPPM Universitas Putera Batam, 2018)
Loading and unloading are the processes which are perform at before and afterwelding process. On this processes, there is a fixture-lifting activity from assembly table move to the Welding machine. The lifting activity as well is perform at after welding process; to uninstall the fixture from the machine then move it to assembly table. This process is performed by 2 persons, because the fixture is quiet heavy, 50 Kg with 40 Inches in diameter and 2.5 inches in the thickness. However, the distance from assembly table to the welding machine is 300 cm. Approximately By this condition, based on The Rapid Entire Body Assesment (REBA) Analysis is resulted Final Score 9 and categorized as a High Risk Level Process. As well based on the scoring of Nordic Body Map (NBM) shows result that there is a high potential pain on the nape, shoulders, arms, back, waist and calves, hence than this activity is consider as Not Ergonomic Process for the worker. Based on the condition as describe above, survey been conducted with Quality Function Deployment (QFD) approach, which concluded that the loading and unloading process is need a lifting tool or equipment to lift up and move the welding fixture. For this purposes to eliminate this difficulty, proposed to have a Lifting Equipment Design could be a trolley or a lifter.